QiShenYiQi Pills, a Compound Chinese Medicine, Ameliorates Doxorubicin-Induced Myocardial Structure Damage and Cardiac Dysfunction in Rats. (27th December 2012) - Tang, Dong-Xin; Zhao, Hai-Ping; Pan, Chun-Shui; Liu, Yu-Ying; Wei, Xiao-Hong; Yang, Xiao-Yuan; Chen, Yuan-Yuan; Fan, Jing-Yu; Wang, Chuan-She; Han, Jing-Yan; Li, Ping-Ping
Abstract : QiShenYiQi Pills (QSYQ) is a compound Chinese medicine used for treatment of cardiovascular diseases. The present study investigated the effects of QSYQ on the Doxorubicin- (DOX-) induced disorders in rat cardiac structure and function and the possible mechanism underlying. A total of 24 male Sprague-Dawley rats were administrated by intraperitoneal injections with DOX at a dose of 2.5 mg/kg, once every day for a total of 6 times. After the 6th injection, the rats were evaluated by echocardiographic analysis, and the animals with injured heart ( n = 14 ) were divided into 2 groups and further treated with ( n = 7 ) or without ( n = 7 ) QSYQ by gavage at a dose of 0.2 g/day, once a day, over the next 2 weeks. Two weeks after QSYQ treatment, the following variables were assessed: myocardial blood flow (MBF) by Laser-Doppler Perfusion Imager, the ratio of heart weight to body weight (HW/BW), myocardial histology, myocardial content of ATP, AMP, free fatty acids (FFAs) and AMP/ATP by ELISA, and expression of PPAR α, PGC-1 α, and ATP 5D by Western blot. Statistical analysis was performed using one-way ANOVA followed by Turkey test for multiple comparisons. DOX challenge significantly increased left ventricular internal diameter and HW/BW and decreased the thickness of the left ventricular posterior wall, the left ventricle ejection fraction, and the left ventricle fractional shortening. DOX also increased AMP, FFA, and AMP/ATP, decreased ATP, and downregulated the protein content of ATP 5D, PPAR α, and PGC-1 α . All these DOX-induced cardiac insults were attenuated significantly by QSYQ treatment. These results show the potential of QSYQ to ameliorate DOX-induced disorders in cardiac structure and function; this effect may be related to the increase in myocardial ATP content via the upregulation of ATP 5D, PPAR α, and PGC-1 α and the oxidation of FFA.